التطورات البيئية المعاصرة وانعكاساتها على نظام الإبلاغ المالي - شبلي عبد الحسين توفيق; يحيى عباس حميد (Journal of Economics and Administrative Sciences, 2013)
Abstract The developments of technology and information that is sweeping the world based on the factors of pressure on the accounting profession in general, and the authors of the accounting information. That becouse the makers of administrative decisions have become in need of new information fit and the environmental situation of the new competition and try to enter new markets, hence the existing system of financial reporting trying to adapt the new situation and trying to overcome criticism of the financial reporting of traditional and which is confined only to the reporting of information Finance and neglect non-financial information, as well as lack of interest in reporting on intangible assets, in addition to not reporting the information for the future. Therefore, to provide objective information and air conditioning system of financial reporting is one of the priorities of the accounting profession in the coming years, because the information that reflect the reality of unity in the knowledge economy is the lifeblood of decision makers in these units